"Victim, survivor, thriver": An exploration of the perceptions and experiences of females previously affiliated with gangs - Lowe, Olivia (2022)
The aim of the current study was to explore the perceptions and experiences of females who have previously been affiliated with gangs using semi-structured interviews and reflective thematic analysis. The research questions focused on women’s experiences and perceptions related to joining the gangs, their relationships in the gang and their desistance from gang affiliation.